PERSEPSI SISWA PADA PENDIDIKAN NILAI DI SEKOLAH DASAR TARBIYATUL ISLAM SAMBAS - Rima Eka Yanti; Aslan Aslan; Asryruni Multahada (CV. ADIBA AISHA AMIRA, 2022)
The development of the era of globalization is tense for educational institutions today, although on the one hand it has had a slight positive impact on educational institutions, so the role of education in instilling positive values is so important. This research is a qualitative research with a field study conducted at the Tarbiyatul Islam Elementary School in Sambas, Sambas District, Sambas Regency. The results showed that some students have differences in understanding the values of aqidah, worship and morals so that there are differences in responding to these values.